2006
DOI: 10.1590/s0103-84782006000400042
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Phakopsora euvitis Ono em Santa Maria, Rio Grande do Sul

Abstract: RESUMO Na safra 2004/05, a ferrugem da videira foi identificada pela primeira vez em parreirais localizados em

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…In South America, the genus Phakopsora has been reported in Colombia, Venezuela and in some areas of Brazil in the last few years (Buriticá 1994;1999;Tessman et al 2004;Bayer & da Costa, 2006;Farr & Rossman, 2019) and now this rust was found parasitizing three distinct varieties of grapevine in rural area in the State of Rio de Janeiro and will be presented.…”
Section: B R Jackes Under Laboratory Conditions and Was Found Infecmentioning
confidence: 86%
“…In South America, the genus Phakopsora has been reported in Colombia, Venezuela and in some areas of Brazil in the last few years (Buriticá 1994;1999;Tessman et al 2004;Bayer & da Costa, 2006;Farr & Rossman, 2019) and now this rust was found parasitizing three distinct varieties of grapevine in rural area in the State of Rio de Janeiro and will be presented.…”
Section: B R Jackes Under Laboratory Conditions and Was Found Infecmentioning
confidence: 86%
“…In South America, the genus Phakopsora has been reported in Colombia, Venezuela and in some areas of Brazil in the last few years (Buriticá 1994;1999;Tessman et al 2004;Bayer & da Costa, 2006;Farr & Rossman, 2019) and now this rust was found parasitizing three distinct varieties of grapevine in rural area in the State of Rio de Janeiro and will be presented. Federal Rural University of do Rio de Janeiro).…”
Section: Introductionmentioning
confidence: 86%
“…Robôs com articulações horizontais (RRP) são conhecidos também como robôs SCARA, e sem sua estrutura de juntas, é composto por duas juntas de rotação e uma prismática. Segundo Bayer (2011), esse robô é dedicado principalmente às atividades de montagem e geralmente possuem 4 graus de liberdade, bastante utilizado na indústria eletrônica para montagem de placas de componentes em placas de circuito impresso.…”
Section: Robótica Industrialunclassified
“…Porém, uma grande desvantagem é que possuem uma cinemática complexa e controle difícil dos movimentos lineares. De acordo com Bayer (2011), por ser bastante versátil, e dotado de uma grande resistência mecânica, é conhecido por ser o modelo mais utilizado na indústria, realizando tarefas como manipulação de componentes, solda, pintura e automação de linhas de produção.…”
Section: Robótica Industrialunclassified